Proteomic and lipidomic analyses reveal novel molecular insights into oat (Avena sativa L.) lipid regulation and crosstalk with starch synthesis during grain development - Lau, Darren; Donnellan, Leigh; Harris, John C.; Hayes, Julie E.; Croser, Janine; Hoffmann, Peter (International journal of biological macromolecules, 2025)
Grain development influences the composition of oat (Avena sativa L.), which impacts the nutritional and processing value of the grains. This study explored the molecular mechanisms underlying oat grain development in two oat varieties – Bannister (10.0 % oil) and Bilby (7.5 % oil), with a focus on lipid biosynthesis, which has not been previously studied at protein level. Matrix-assisted laser desorption and ionisation mass spectrometry imaging (MALDI-MSI) of developing grains revealed oil distribution within the developing endosperm, where starch is also expected to accumulate. Shotgun lipidomics and proteomics were performed throughout development (from 4 to 20 days after pollination (DAP) and at maturity) to examine the temporal dynamics of lipid biosynthesis. More than 4500 protein groups were identified. Clustering of proteins based on their temporal expression patterns revealed the upregulation of major synthesis pathways from 8 DAP onwards, marking a critical stage in oat grain development. Triacylglycerol (TG) abundances strongly correlated with the expressions of enzymes involved in fatty acid synthesis (FAS), highlighting a bottleneck pathway in oat oil synthesis. Bannister displayed higher glycerolipid accumulation than Bilby, which was linked to the upregulation of enzymes in FAS and TG assembly pathways. Differences in the levels of lipid and starch synthesis enzymes between the two varieties exemplified a possible divergence in metabolic priorities during seed development. These findings provide insights into the regulation of lipid synthesis pathways in oats and lay a foundation for future studies investigating factors influencing grain composition to meet the future needs of an expanding industry.